2002
DOI: 10.1523/jneurosci.22-21-09475.2002
|View full text |Cite
|
Sign up to set email alerts
|

Response of Neurons in the Lateral Intraparietal Area during a Combined Visual Discrimination Reaction Time Task

Abstract: Decisions about the visual world can take time to form, especially when information is unreliable. We studied the neural correlate of gradual decision formation by recording activity from the lateral intraparietal cortex (area LIP) of rhesus monkeys during a combined motion-discrimination reaction-time task. Monkeys reported the direction of random-dot motion by making an eye movement to one of two peripheral choice targets, one of which was within the response field of the neuron. We varied the difficulty of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

244
1,907
14
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,449 publications
(2,167 citation statements)
references
References 47 publications
244
1,907
14
2
Order By: Relevance
“…2a,b). On both stimulation and non-stimulation trials, stronger motion toward T in led to more T in choices, and stronger motion toward T out led to more T out choices, as previously shown 10 . Microstimulation caused a small change in these choice frequencies.…”
Section: Lip Microstimulation Affects Choice and Reaction Timesupporting
confidence: 75%
See 2 more Smart Citations
“…2a,b). On both stimulation and non-stimulation trials, stronger motion toward T in led to more T in choices, and stronger motion toward T out led to more T out choices, as previously shown 10 . Microstimulation caused a small change in these choice frequencies.…”
Section: Lip Microstimulation Affects Choice and Reaction Timesupporting
confidence: 75%
“…2c,d). On both stimulation and nonstimulation trials, stronger motion led to faster RTs for both T in and T out choices, compared to the more difficult conditions, as has been previously shown 10 . The first effect of microstimulation on decision time was a reduction in RT for T in choices (Fig.…”
Section: Lip Microstimulation Affects Choice and Reaction Timesupporting
confidence: 74%
See 1 more Smart Citation
“…Human studies, for example, show that areas such as the motion-sensitive region MT+, supplementary motor area (SMA), and intraparietal sulcus (IPS) all display this parametric effect. Importantly, results from macaque studies show that activity in lateral intraparietal area (LIP), the macaque homologue of IPS (Grefkes and Fink, 2005), accords with predictions of the diffusion model and covaries with behavior (Roitman and Shadlen, 2002), consistent with previous macaque work demonstrating a link between LIP activity and response selection (reviewed in Andersen et al, 1997). In contrast, recordings in the macaque homologues of MT+ and SMA implicate them in either sensory (Gold and Shadlen, 2007) or motor (Mita et al, 2009) tasks, respectively.…”
supporting
confidence: 78%
“…Previous work in primates has also suggested that IPS is important for sensorimotor transformations, rather than exclusively sensory or motor representations. Neuronal activity within the macaque homologue of mIPS, the lateral intraparietal area (LIP; Grefkes and Fink, 2005), correlated with the predictions of a diffusion model for evidence accumulation to threshold (Roitman and Shadlen, 2002;Shadlen and Newsome, 2001), thereby linking sensory information with the response. Moreover, microstimulation of LIP neurons that showed accumulation-related activity toward a specific direction increased the choice of that direction only when the stimulus was presented (Hanks et al, 2006), indicating that this area requires sensory information to influence motor response.…”
Section: Discussionmentioning
confidence: 77%